A Virtual Space Built on a Canvas Painting for an “Augmented” Experience to Catch the Artist’s Message - Capotorto, Salvatore; Lepore, Maria; Varasano, Antonietta (ISPRS international journal of geo-information, 2021)
“Entering” a canvas to examine and learn about the work from unexplored points of view is an experiential “journey” in an environment reconstructed through the use and integration of innovative technologies, such as descriptive geometry and digital photogrammetry, solid modeling and immersive photography. Generating a “sense of presence” in the viewer means connecting it with immediacy to the artist’s message and grasping even the most subtle elements of the painting that are difficult to understand, such as architectural inconsistencies or the play of perspectives that, very often, bring out the situations scripted, characterized by discoveries that prelude to the aesthetic pleasure as the multiplicity of meanings and the “stylistic overcoding” of the work is revealed. The research hypotheses were applied to a case study, or to the splendid “Last Supper” by the Flemish artist Gaspar Hovic, a canvas painted in oil (late 15th century AD) and kept in the Matrice SM Veterana Church di Triggiano (BA), where the representation of the suggestive moment of Jesus with the Apostles is carried out through numerous symbols, in an evocative architectural context rich in details. The pictorial subject provides a series of very interesting ideas suitable for research of the role of perspective. The inverse method of linear perspective was used to reveal the plants and sections corresponding to the perspective space of the painting, used as the basis for the reconstruction of the 3D model of the entire scenic composition. Although the painting represents the apparently rigorous application of the perspective technique, by “entering” the canvas it is possible to observe some exceptions to the geometric rules deliberately introduced by the artist, thus making the perspective restitution process an effective interpretative act of the work.